Building Sustainable Capacity for Disease Diagnosis in Sub-Saharan Africa: Case Studies of Cooperation in Diagnostic Pathology - Mariani-Costantini, Renato; Awadelkarim, Khalid Dafaallah; Barberis, Massimo; Clemente, Claudio; Blasio, Pasquale De; Gioacchino, Mario Di; Faravelli, Agostino; Forni, Marco; Grigolato, Piergiovanni; Leoncini, Lorenzo; Schuerfeld, Karin; Mohamedani, Ahmed Abdalla; et al. (IntechOpen, 2011)
None